The Impact of Principals’ Motivation and Self-Regulation on Teachers’ Job Satisfaction - Qazi Muhammad Nadeem; Dr. Allah Noor Khan; Aleeza Gul (Journal of Religion and Society, 2025)
This study investigates the relationship between teachers' perceptions of their principals' leadership qualities specifically motivation and self-regulation and principals’ perceptions about their teachers’ job satisfaction. Data were collected from 48 teachers and 18 principals across 18 secondary schools using perceptual scales. Descriptive statistics revealed a sample with exceptionally high and uniformly positive ratings for principals’ motivation and self-regulation. Similarly, the teachers’ job satisfaction was perceived high by their principals. Pearson correlation analysis identified strong, statistically significant positive relationships between both leadership variables and job satisfaction (*r* = .60 for each). A multiple regression model confirmed that, collectively, principals' motivation and self-regulation explained a significant portion (21.8%) of the variance in teacher job satisfaction. The findings conclusively affirm that higher perceived levels of these specific leadership competencies are strongly associated with higher teacher job satisfaction in the studied context. Based on these results, it is recommended that school leadership development programs prioritize cultivating both motivational and self-regulatory skills. Future research should seek to generalize these findings in more diverse settings, employ longitudinal designs to establish causality, and develop integrated models incorporating additional contextual factors influencing teacher well-being. Key Words: Principals, Emotional Intelligence, Motivation, Self-Regulation, Teachers, Job Satisfaction